COMPARATIVE ANALYSIS OF THE INFLAMMATORY RESPOND OF THE VASCULAR WALL AFTER IMPLANTATION OF BIORESORBABLE SCAFFOLDS AND EVEROLIMUS COVERED STENTS IN PATIENTS WITH STABLE CORONARY ARTERY DISEASE - N. A. Musikhina; T. I. Petelina; I. S. Bessonov; N. A. Galeeva; E. A. Gorbatenko; A. I. Kostousova (Сибирский научный медицинский журнал, 2019)
Aim - to conduct a comparative analysis of markers of inflammatory reaction of the vascular wall in patients with stable coronary artery disease (CAD) after implantation of bioresorbable scaffolds (BS) and everolimus-eluting stents during short observation period. Material and methods. 20 patients with stable CAD and mono-vessel coronary bed lesion with indication to percutaneous coronary intervention (PCI) were studied. Group 1 consisted of 9 patients with implanted stent covered with everolimus; group 2 consisted of 11 patients with implanted BS. Biochemical inflammatory markers were defined at the admission time, in 1 day, 4 days and 1 month after PCI. Results. In 1 day after PCI both groups expectedly showed cytokine level growth, including interleukin 6 (IL-6), as a respond to the vascular wall lesion with the following decrease in 4 days to the initial level. On the second day after PCI serum content of matrix metalloproteinases 9 (MMPs-9) was increased in groups 1 and 2 of patients. Lowering of MMPs-9 with no reaching the initial level in 1 month was noticed only in group 2, whereas group 1 kept high concentration of MMPs-9. The comparable groups had the maximum content of soluble CD40-ligand (sCD40L) on the 4th day with a little lowering after 1 month only in group 2. High level of high-sensitive C-reactive protein (CRP) remained during the entire follow-up period in both groups. Conclusion: Patients with stable CAD after implantation of BS and everolimus covered stents did not have any differences in dynamics of mediators of acute inflammation phase. Persistent high levels of MMPs-9, sCD40L and also elevated concentration of CRP assume prolonged character of the vascular wall inflammatory respond, being more expressed after implantation of everolimus covered stents.